FACTOR ANALYSIS OF THE ROLLING PROCESS TECHNOLOGY (Part2) - A. N. Chichko; L. A. Fekoistova; V. I. Shcherbakov; A. V. Vedeneev (Литьë и металлургия, 2011)
The mathematical model of the multivariate regression analysis carrying out is presented. Its practical application for rolled production is examined. Analysis of the model adequacy is carried out.